Variation of HLA class I (-A and -C) genes in individuals infected with hepatitis B or hepatitis C virus in Cameroon. Issue 10 (October 2020) - Yengo, Clauvis Kunkeng; Torimiro, Judith; Kowo, Mathurin; Lebon, Patrick Awoumou; Tiedeu, Barbara Atogho; Luma, Henry; Njoya, Oudou; Rowland-Jones, Sarah; Yindom, Louis-Marie
Abstract: The Human Leucocyte Antigens (HLA) work in concert with other immune factors to modulate immunity to viral infections. Extensive variation has been reported in the genetic sequences and functions of classical HLA class I genes in many (mostly Western) populations, and several HLA associations with infectious disease outcomes have been reported. Little is known about their role in the susceptibility or resistance to hepatitis viruses in Central African populations. The aim of this study was to determine variants of two HLA class I genes (HLA-A and -C) in adults infected with hepatitis B (HBV)- or -C (HCV) virus in Cameroon. In this case-control study, a total of 169 unrelated adults comprising 68 HCV-infected, 38 HBV-infected and 63 uninfected (controls) individuals participated. Each consented participant was screened for HBV, HCV, and HIV infections and willingly donated a single blood sample for genomic DNA isolation and some clinical laboratory tests. HLA-A and HLA-C were genotyped using previously described sequence-based techniques (SBT). A total of 54 HLA alleles were identified in the study population (27 HLA-A and 27 HLA-C). HLA-A∗23:01 and HLA-C∗07:01 were the most common alleles with genotype frequencies of 31.4% and 29.3%, respectively. Hepatitis individuals were six times more likely to be HLA-A∗30:01 carriers than uninfected controls (OR = 6.30, p = 0.020 (HBV); OR = 6.21, p = 0.010 (HCV), respectively). Similarly, carriers of HLA-C∗17:01 were over-represented in the HBV-infected compared to the uninfected control group (21.9% vs. 6.4%, respectively) suggesting that this allele could play a role in the susceptibility to HBV infection. These findings demonstrate that carriers of HLA-A∗30:01 were over-represented in the hepatitis group compared to uninfected controls while HLA-C∗17:01 was completely absent in the HCV + group. Abstract : Cell biology; Immunology; Clinical genetics; Genetics; Molecular biology; HLA; HBV; HCV; Association study; Cameroon